2014
DOI: 10.1111/afe.12069
|View full text |Cite
|
Sign up to set email alerts
|

Succession of saproxylic beetles associated with decomposition of boreal white spruce logs

Abstract: 1 We reared saproxylic beetles from 54 white spruce [Picea glauca (Moench) Voss] logs collected in northwestern Alberta, Canada. Logs represented six decay classes, ranging from freshly dead to well decayed. 2 Beetle assemblages were indicated mainly by phloeophagous and predaceous species in early decay stages, although indicator species were mainly predaceous in later stages of decay. No indicator species were identified for intermediate decay stages. 3 Larvae from rearings were disproportionately predaceous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…We also fitted linear models to test for management strategy effects on tree species composition, basal area and log-transformed deadwood volume. Since the quality of deadwood might have a higher impact than the quantity on beetles assemblages [ 31 , 52 ], we divided deadwood into decay stages and substrate types to compare effects of management strategy on deadwood type using the R package ‘nlme’. A principal component analyses (PCA) were performed to assist in the interpretation of effects from management of stand characteristic using the R-package ‘ factoextra’ [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also fitted linear models to test for management strategy effects on tree species composition, basal area and log-transformed deadwood volume. Since the quality of deadwood might have a higher impact than the quantity on beetles assemblages [ 31 , 52 ], we divided deadwood into decay stages and substrate types to compare effects of management strategy on deadwood type using the R package ‘nlme’. A principal component analyses (PCA) were performed to assist in the interpretation of effects from management of stand characteristic using the R-package ‘ factoextra’ [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…As decay progresses, the chemical composition and nutrient availability change [ 29 ] and decay stages last longer, e.g., it can take up to 50 years for a spruce log to reach the advanced stages of decay [ 30 ]. This means that rapid recolonization becomes less important for species dependent on late decay stages [ 31 , 32 ], but that resources may be much rarer following silviculture, increasing the vulnerability of these species. Previous research from our study system indicated that even-aged forest management has limited impacts on beetle assemblages compared with uneven-aged forest management [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, we also separately analyzed saproxylic species that we caught (even though pitfall trapping is not a recommended method of collection for such species, although it has been used to look at certain species such as pine weevil). We would expect saproxylic abundance to be highest in the first year and diversity to increase with stump age (Jonsell et al ., ; Stenbacka et al ., ; Lee et al ., ). Stump‐harvesting is a two‐three stage process: once stumps are removed from the soil, they are temporarily left on site in wind‐rows to undergo a ‘weathering period’.…”
Section: Introductionmentioning
confidence: 97%
“…The enhancement of soil macroarthropod communities in the PC treatment can be related to several non-mutually exclusive mechanisms, several of which are related to how dead wood can enhance soil biota. First, as the logs decompose, they lose integrity, causing the wood to crumble and increasing the amount and heterogeneity of resources available for taxa involved in wood decay, such as wood-boring beetles (Coleoptera) [78] and termites (Termitoidae) [79]. Logs had lost an overall 23% of their mass at the time of the present study, and they showed a high degree of fragmentation and many tunnels bored by insects [80].…”
Section: Differences Between Dead-wood Treatmentsmentioning
confidence: 82%